The Effect Of Submerged Salt And Atung (Parinarium glaberium, Hassk) On The Quality Of Dried Salted Skipjack Tuna (Katsuwonus pelamis, Linn) - Moniharapon, Trijunianto; Pattipeilohy, Fredy; Moniharapo, Erynola (Universitas Negeri Gorontalo, 2022)
The purpose of this study was to determine the effectiveness of submerged salt and atung (Parinarium glaberimum, Hassk) on the quality of dry salted skipjack tuna (Katsuwonus pelamis, Linn.). The treatment consisted of 2 factors, namely salt concentration (5, 10%) and atung concentration (3.4 and 5%). Data were analyzed using RAL (Completely randomized design followed by BNJ test. Parameters seen were water content, protein content, salt content and TPC content.The concentration of 10% atung 5% salt immersion was effective in producing water content, protein content, salt content and TPC content of dry salted skipjack tuna in order, namely: 28.31%; 67.02%; 4.60% and 6.2 x 103 colonies; salt 10% atung 4%: 27.68%; 68.63%; 3.65% and 2.0 x 104 colonies; salt 10% or 3%: 27.38%; 69.23%; 3.10% and 5.9 x 103 colonies; salt 5% atung 5%: 27.30%; 66.23%; 5.25% and 5.9 x 103 colonies; salt 5% atung 4%: 30.54%; 65.94%; 2.95% and 3.6 x 103 colonies; salt 5% atung 3%: 28.80%; 65.20%; 5.20% and 1.9 x 104 colonies; and 25% control: 32.34%; 54.31%; 13.5% and 2.3 x 103 colonies. Protein denaturation that occurred in the processing of dried salted skipjack tuna with salt and atung graded immersion treatment was between about 1.6 - 7.3%, while the control was 22.8%.